Perceptions of Prostate Cancer Screening Controversy and Informed Decision Making: Implications for Development of a Targeted Decision Aid for Unaffected Male First-Degree Relatives. Issue 6 (July 2015) - Gwede, Clement K.; Davis, Stacy N.; Wilson, Shaenelle; Patel, Mitul; Vadaparampil, Susan T.; Meade, Cathy D.; Rivers, Brian M.; Yu, Daohai; Torres-Roca, Javier; Heysek, Randy; Spiess, Philippe E.; Pow-Sang, Julio; et al.
Purpose: First-degree relatives (FDRs) of prostate cancer (PC) patients should consider multiple concurrent personal risk factors when engaging in informed decision making (IDM) about PC screening. This study assessed perceptions of IDM recommendations and risk-appropriate strategies for IDM among FDRs of varied race/ethnicity. Design: A cross-sectional, qualitative study design was used. Setting: Study setting was a cancer center in southwest Florida. Participants: The study comprised 44 participants (24 PC patients and 20 unaffected FDRs). Method: Focus groups and individual interviews were conducted and analyzed using content analysis and constant comparison methods. Results: Patients and FDRs found the PC screening debate and IDM recommendations to be complex and counterintuitive. They overwhelmingly believed screening saves lives and does not have associated harms. There was a strongly expressed need to improve communication between patients and FDRs. A single decision aid that addresses the needs of all FDRs, rather than one separating by race/ethnicity, was recommended as sufficient by study participants. These perspectives guided the development of an innovative decision aid that deconstructs the screening controversy and IDM processes into simpler concepts and provides step-by-step strategies for FDRs to engage in IDM. Conclusion: Implementing IDM among FDRs is challenging because the IDM paradigm departs from historical messages promoting routine screening. These contradictions should be recognized and addressed for men to participate effectively in IDM. A randomized pilot study evaluating outcomes of the resulting decision aid is underway.